2014
DOI: 10.1002/chem.201304344
|View full text |Cite
|
Sign up to set email alerts
|

SnIV Porphyrin Scaffolds for Axially Bonded Multiporphyrin Arrays: Synthesis and Structure Elucidation by NMR Studies

Abstract: A simple, one-step, supramolecular strategy was adopted to synthesize Sn(IV) -porphyrin-based axially bonded triads and higher oligomers by using meso-pyridyl Sn(IV) porphyrin, meso-hydroxyphenyl-21,23-dithiaporphyrin, and Ru(II) porphyrin as building blocks and employing complementary and non-interfering Sn(IV) O and Ru(II) ⋅⋅⋅N interactions. The multiporphyrin arrays are stable and robust and were purified by column chromatography. (1) H, (1) H-(1) H COSY and NOESY NMR spectroscopic studies were used to une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…As expected, the main consequence of the axial coordination to the metallo-porphyrins, is a remarked upfield shift of the proton resonances of the axially bound porphyrin, compared to the parent free system, with an extent that decreases as the proton distance from the Sn­(IV) porphyrin plane increases (e.g., Δδ = −3.08, H a ; −1.15, H b ; −0.71, Hβ 1 ; and −0.29, Hβ 2 ), as already described previously for similar side-to-face assemblies. ,, The 19 F NMR spectrum of 4 (CDCl 3 Figure S14) is not particularly informative, with features practically unvaried as compared to those found for the parent SnTpPF­(OH) 2 porphyrin.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As expected, the main consequence of the axial coordination to the metallo-porphyrins, is a remarked upfield shift of the proton resonances of the axially bound porphyrin, compared to the parent free system, with an extent that decreases as the proton distance from the Sn­(IV) porphyrin plane increases (e.g., Δδ = −3.08, H a ; −1.15, H b ; −0.71, Hβ 1 ; and −0.29, Hβ 2 ), as already described previously for similar side-to-face assemblies. ,, The 19 F NMR spectrum of 4 (CDCl 3 Figure S14) is not particularly informative, with features practically unvaried as compared to those found for the parent SnTpPF­(OH) 2 porphyrin.…”
Section: Resultssupporting
confidence: 84%
“…Sn­(IV) porphyrins are an excellent choice as scaffolds for the construction of light-responsive supramolecular assemblies because of a series of peculiar and convenient properties: (i) a strong absorption in the visible region, (ii) an intense fluorescence, (iii) a reversible redox behavior, (iv) relative ease of reduction, (v) a diamagnetic nature, plus a central NMR active nucleus, and (vi) a notable preference to form two strong axial bonds with oxygen anionic ligands . In particular, the latter feature has been exploited by several research groups to efficiently construct multiporphyrin adducts of various complexity, via axial coordination of phenolate or benzoate functions of many different types of organic fragments, such as metallo-porphyrins and free-base porphyrins. Recently, Guldi and co-workers reported on the synthesis of multichromophoric arrays consisting of two bodipy units axially bound to a Sn­(IV) porphyrin . An ultrafast photophysical investigation revealed that, in these systems, photoinduced electron and/or energy transfer processes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…These carboxylic groups are utilized to form amide linkages with porphyrins in later stages. 189,190 Fig. 20 Schematic of porphyrin-CNH hybrids.…”
Section: Porphyrin-graphene Hybridsmentioning
confidence: 99%
“…They include carotenoids, betalains, flavonoids, and chlorophyll. However, natural dyes have low efficiency because of weak bonding with the semiconductor surface [75], [76]. Efforts to improve their efficiency include mixing two or more pigments to increase their light absorption capability and using different solvents to improve dye extraction and bonding between the dye molecule and semiconductor surface [77].…”
Section: Sensitization Mechanismmentioning
confidence: 99%